Spatial Assessment of Ambient Air Pollution and Associated Health Risks in Selected Communities of Abia State, Nigeria - Esther Chimezie Akandu (IIARD INTERNATIONAL JOURNAL OF GEOGRAPHY AND ENVIRONMENTAL MANAGEMENT, 2026)
Air pollution is an emerging environmental health concern in rapidly urbanizing regions of developing countries. This study assessed ambient air pollution levels and associated health risks in selected communities of Abia State, southeastern Nigeria. Field monitoring was conducted across multiple sampling locations representing residential, commercial, and traffic-dominated environments. Concentrations of major atmospheric pollutants including particulate matter (PM₂.₅ and PM₁₀), carbon monoxide (CO), carbon dioxide (CO₂), nitrogen dioxide (NO₂), hydrogen sulphide (H₂S), and volatile organic compounds (VOCs) were Introduction measured using portable air quality monitoring devices. Spatial distribution patterns were analyzed using Geographic Information Systems and descriptive statistical methods. Air Quality Index (AQI) values were computed to evaluate potential health risks. Results indicated significant spatial variation in pollutant concentrations across the study area, with higher levels recorded in densely populated and high-traffic areas. PM₂.₅ and PM₁₀ concentrations in several locations exceeded recommended limits of the World Health Organization, indicating potential health risks to residents. AQI classification showed that some locations fall within the moderate to unhealthy categories. Multiple linear regression analysis revealed that vehicular emissions, commercial activities, and generator use were significant predictors of pollution levels. The study highlights the need for continuous air quality monitoring, effective emission control policies, and improved urban environmental management strategies in Abia State.